Global research trends in endometrial receptivity from 2000 to 2024: bibliometric analysis - Liu, Ziping; Zhang, Zelin; Xie, Ping (Frontiers in Medicine, 2024)
Background In recent years, extensive research has been conducted on endometrial receptivity (ER), with rapidly evolving research hotspots and trends. Our study aimed to explore the development of ER research from 2000 to the present and provide insights for future endeavors. Materials and methods Relevant research publications on ER from 2000 to 2024 were retrieved from the Web of Science Core Collection (WOSCC) database. CiteSpace, VOSviewer and Excel tools were employed to conduct the bibliometric analysis. Results A total of 3,354 articles were analyzed, revealing an overall upward trend in annual publication numbers, signifying the increasing attractiveness and research value of this field. Globally, China led with a notable advantage of 1,030 publications, followed by the United States (650) and Spain (251), constituting the first tier of international research. Valencia University topped the list of institutions with 108 publications, closely followed by Shanghai Jiao Tong University with 87. Fertility and Sterility (IF6.6, Q1) is the one with the largest number of publications, accounting for 7.96% of the total publications. The three most co-cited journals were Fertility and Sterility, Biology of Reproduction, and Human Reproduction. A co-citation reference analysis revealed that ER research can be categorized into ten major subfields, including embryo implantation, frozen embryo transfer, integrins, recurrent implantation failure, intrauterine adhesions, etc. Since 2020, the keywords with the strongest citation bursts include repeated implantation failure and frozen. Conclusion This study employs bibliometric analysis to offer researchers in the field of ER a comprehensive perspective. Since 2000, there has been a remarkable surge in the number of publications in the ER research field. These studies primarily concentrate on delving into the pathophysiological mechanisms of ER, with the primary objective of enhancing clinical pregnancy rates and live birth rates, benefiting more infertile patients. Currently, addressing the ER issues in patients with recurrent implantation failure represents the forefront of research. The primary treatment approaches currently in use involve optimizing embryo transfer timing and employing innovative strategies such as immunotherapy. These cutting-edge analyses not only provide new insights into the treatment of ER but also offer researchers fresh research directions, and staying abreast of the latest trends and advancements in the field.